A Nanocapsule‐Based Approach Toward Physical Thermolatent Catalysis. Issue 30 (11th May 2016) - Bijlard, Ann‐Christin; Hansen, Anne; Lieberwirth, Ingo; Landfester, Katharina; Taden, Andreas
Abstract : Performance under pressure is utilized as a key concept for colloidal control of reaction kinetics. Barrier nanocapsules containing a catalyst and a low‐boiling‐point release agent enable a highly desired, adjustable, and distinct non‐Arrhenius behavior for thermoset curing.